Anterior segment injury by a high-power handheld blue laser device - Al-Armary, Mohammad A. (2017)
Purpose: To report a case of severe anterior segment inflammation secondary to exposure to a high-power blue laser device. Methods: Case report. Results: A 14-year-old male presented with redness, pain and decreased vision in his left eye after exposure to blue laser. Examination indicated severe conjunctival injection associated with 4+ cells in the anterior chamber with fibrinous reaction. The posterior pole was normal. Conclusion: Blue laser devices are easily available through the Internet. These devices can cause devastating ocular injuries. National safety guidelines are required to regulate use.